The Influence of Financial Technology Growth on Monetary Policy in Developing Economies - Lia Sari Oktara (Indonesian Journal of Research and Service Studies, 2024)
This study aims to evaluate the influence of financial technology (fintech) development on the effectiveness of monetary policy in developing countries and identify the challenges and opportunities posed to central banks. The research employs a critical literature review of empirical studies and reports from various countries, focusing on the impact of fintech on monetary policy transmission, financial system stability, and financial inclusion. Studies indicate that fintech can influence the demand and supply of money, create new monetary policy transmission channels, and enhance efficiency and financial inclusion. Key findings reveal that fintech can strengthen monetary policy transmission and promote financial inclusion, but also heighten risks to financial stability, such as credit, liquidity, and operational risks. This article emphasizes the need for an adaptive regulatory and supervisory approach, along with innovation in monetary policy, such as the development of a Central Bank Digital Currency (CBDC), to respond to fintech developments and maximize its benefits for the economy. CBDC development needs to consider various aspects, including design, implications for stability and monetary policy transmission, and an appropriate regulatory and supervisory framework.